(3cJGH aj GdSjGSI hGdCOHs - (3GdhdjO Hf eMeO GdJOeQj, CHh GdYHGSs
(3ChdgG (B:s
(3Ef Chd eG CaJJJM Hg GdcdGe hCMb eG GQJHWJ Hg GdfYe eG GaJJM Gddg Hg cJGH hNJe Hg OYGA Cgd LfJg s
(3BNQgG (B:s
(3hfMf fNJe cJGHfG HeG GSJaJMfGg Hg ef GdMeO hGdKfGA Ydjg hGdMeO ddg QH GdYGdejf cKjQkG ceG gh Cgdg s
(3Cdag ai SfI (B406s
(3hLYdg ai eGFI HGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs